2022
DOI: 10.1038/s41598-022-07770-8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-nuclear antibody and a granuloma could be biomarkers for iCIs-related hepatitis by anti-PD-1 treatment

Abstract: It has been reported that various kinds of immune checkpoint inhibitors (iCIs) could induce immune-related liver damage. We should focus on the programmed cell death-receptor-1 (PD-1) antibody and non-small cell lung cancer (NSCLC) to analyze the characteristics of hepatitis related to iCIs and find factors that could be useful biomarkers for the diagnosis. A single-center retrospective study of 252 NSCLC patients who received PD-1 antibody (nivolumab or pembrolizumab). Some of the biochemical markers and immu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…The copyright holder for this preprint this version posted August 17, 2023. ; https://doi.org/10.1101/2023.08.17.553694 doi: bioRxiv preprint immune-checkpoint inhibitors (ICIs) like nivolumab or pembrolizumab [22,23,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted August 17, 2023. ; https://doi.org/10.1101/2023.08.17.553694 doi: bioRxiv preprint immune-checkpoint inhibitors (ICIs) like nivolumab or pembrolizumab [22,23,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that for patients treated with nivolumab, positive ANA testing was identified as a risk factor for ICI-related hepatitis (risk ratio 2.133: 95% CI 1.085-4.194: p=0.0281). On the other hand, for patients receiving pembrolizumab, both positive ANA and age were found to be potential risk factors for ICIS-related hepatitis (risk ratios 7.834: 95% CI 1.743-35.21: p=0.0073 and 0.896: 95% CI 0.896: p=0.0050, respectively) [101]. Predicting immunemediated hepatitis is relatively difficult, and primary liver diseases and other causes of liver function abnormalities should be excluded first.…”
Section: Ici-associated Hepatitismentioning
confidence: 99%
“… 125 The presence of pre-existing antinuclear antibodies along with granulomas on histology may serve as potential markers of ICI-related hepatitis. 126 …”
Section: Etiologymentioning
confidence: 99%